Latina Shikhara (mono-spire superstructure) of the side shrine - Temples of India Project Team (Jio Institute, 2024)
The latina shikhara (mono-spire superstructure) of the side shrine of the Triple-shrine Temple still has two bhumi khandas (tiers) on its south-facing elevation. All the latas (bands) of the shikhara are composed of combinations of gavaksha (dormer window) designs. The east-facing side of the temple has a protruding shukanasa (projection over the entrance of the sanctum) which is connected to the main shikhara and acts as the superstructure of the mandapa (pillared hall) of the temple. The corner bands of a latina shikhara are called venukosha. This is made up of tiers of diminishing sizes. Each of these tiers is separated by a flat ribbed disc known as the amalaka.